Metode Simulated Annealing untuk Optimasi Penjadwalan Perkuliahan Perguruan Tinggi - Sari, Wiktasari; Suseno, Jatmiko Endro (Universitas Diponegoro, 2016)
Course scheduling an assignment of courses and lecturers in the available time slots involving certain restrictions. Simulated annealing is a heuristic method can be used as search method and provide acceptable solutions with good results. The research aims to make scheduling courses at the college using simulated annealing using five variables data that lecturer courses, the time slot is comprised of the day and the time period and class room. The research has two objective functions to be generated, the first is the assignment of a lecturer on courses that will be of teaching, second lecturers and their assignment course on the time slot and the room available. The objective function is calculated by taking into account the restrictions involved to produce the optimal solution. The validation is performed by testing to simulated annealing method with an varian average of 77.791% of the data variance can reach a solution with a standard deviation of 3.931509. In this research given the method of solution in the use of the remaining search space to be reused by the data that is unallocated.